Analysis of Occupational Health and Safety (OHS) on the Cable Tray Support Farming MSP Fabrication Project Using the Hazard Identifications and Risk Assessment (HIRA) and Hazard and Operability (HAZOP) Methods - Salsabila, Cindy Aulia; Andesta, Deny (JTI: Jurnal Teknik Industri, 2024)
A cable tray project is one of the joint ventures that PT. Swadaya Graha and PT. Triraya have finished. Workplace mishaps are unavoidable when working on a project. There were multiple work accidents on the cable tray construction project from February 2023 to May 2023, according to the work accident report of PT. Swadaya Graha. One of these workplace mishaps leaves a victim with minor wounds and burns. In order to encourage employees to stay vigilant and exercise caution whenever working on a project, this research was done to reduce the likelihood of workplace accidents and to learn about the possible risks associated with working on a cable tray project. Using the methods of Hazard Identification and Risk Assessment (HIRA) and Hazard and Operability (HAZOP), this study located potential danger sources in the cable tray project work. This investigation produced 35 potential hazard findings, including 5 dominant potential hazards (hazards with the highest level value) and several recommendations for corrective measures that could benefit the company, such as adhering to the SOP that has been established. Keywords: Work Accidents, Potential Hazards, Cable Tray, HAZOP, HIRA